2009
DOI: 10.1186/1465-9921-10-122
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, lung function and airway inflammation in Mexico City school children exposed to air pollutants

Abstract: IntroductionAir pollutant exposure has been associated with an increase in inflammatory markers and a decline in lung function in asthmatic children. Several studies suggest that dietary intake of fruits and vegetables might modify the adverse effect of air pollutants.MethodsA total of 158 asthmatic children recruited at the Children's Hospital of Mexico and 50 non-asthmatic children were followed for 22 weeks. Pulmonary function was measured and nasal lavage collected and analyzed every 2 weeks. Dietary intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 46 publications
7
91
0
2
Order By: Relevance
“…However, increased in WC, WHR and WHtR was observed with increased fruit intake which was not expected. correlated with lung function (FEV1-FVC) among adults in both a cohort study [76] and a cross-sectional study [77] [78], as well as among children in a crosssectional study [40], and a cohort study [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increased in WC, WHR and WHtR was observed with increased fruit intake which was not expected. correlated with lung function (FEV1-FVC) among adults in both a cohort study [76] and a cross-sectional study [77] [78], as well as among children in a crosssectional study [40], and a cohort study [42].…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanism behind such a relationship is also unclear [37] [38] [39]. In addition, many cross-sectional studies have shown that F & V intake is correlated with improved lung function in children, which may be related to the high content of Vitamin C [40] [41] [42]. F & V are considered to have a rich content of antioxidants, like Vitamin C; and if taken in large amounts can lead to better lung functioning as antioxidants modulate the adverse effect of ozone (O 3 ) on lung function as well as the resulting airway inflammatory response [41].…”
mentioning
confidence: 99%
“…[44][45][46] Other studies have focused on global diet instead of vitamins or nutrients, reporting that fast food 47 or a 'Western' dietary pattern 48 is associated with higher asthma risk in Mexico and Brazil, while higher fruit and vegetable intake or a 'Mediterranean' diet is associated with reduced airway inflammation and higher lung function in Mexican children. 49 In one of few clinical trials of nutrients and asthma in Latin America, docosahexaenoic acid supplementation in the second and third trimesters of pregnancy led to lower risk (aOR=0.76, Figure 1 Prevalence of childhood asthma in Latin America. 5 7-9 Prevalence in the Dominican Republic is based on adult asthma.…”
Section: Diet and Obesitymentioning
confidence: 99%
“…A diet rich in fish is associated with elevated levels of selenium and zinc [80] and in many Latin American populations, wherein fish is frequently cooked in palm oil, with high levels of vitamin A. Selenium, zinc and vitamin A have antioxidant effects and have been associated with protection against asthma [75]. In Latin America, data from Mexico showed that children adherent to a 'Mediterranean' diet have less asthma [79,81]. Data from urban Brazil showed a one-third reduction in the prevalence of nonatopic asthma associated with fish consumption (S. D'Innocenzo, M.L.…”
Section: Diet and Obesitymentioning
confidence: 99%